Social Representations on Lithuanian Women Leaders in the STEAM Fields: A Critical Discourse Analysis - Buelvas-Baldiris, Tatiana; Rubira-García, Rainer; Pocevičienė, Rasa (Information & Media, 2023)
Science, technology, engineering, arts, and mathematics (STEAM) are fields substantially crucial for innovation and development. Nevertheless, the gender gap in these areas is significant also in European countries. Considering the underrepresentation of STEAM women’s leadership, we provide insight into the common characteristics that led Lithuanian women to become referents in their fields. We identify elements of leadership in discursive social representations, professional ideologies, gender identity and role congruency in connection to power structures from a gender perspective within organisations, considering the mediations of the social context. We conducted the research in two phases: an online questionnaire and in-depth interviews. We performed a critical discourse analysis of Lithuanian Women’s testimonies to understand gender social representations. Parenthood highly influences building leadership and choosing STEAM careers, whereas self-efficacy and creativity are essential elements. High co-responsibility at home confirms that family context is vital. In STEAM careers, a male-centric perspective still constrains female leadership. There is still work to be done regarding active politics, programs, and law enforcement to create equity and social justice relationships between men and females, especially in STEAM areas.
Keywords: Women leadership; Social Representations; STEAM; Gender studies; Lithuania